The effect of the planting depth of cuttings on biomass of short rotation willow. Issue 2 (4th March 2017) - Han, Qingmin; Harayama, Hisanori; Uemura, Akira; Ito, Eriko; Utsugi, Hajime
ABSTRACT: In order to investigate how the depth to which a cutting is inserted into the ground influences biomass of short-rotation coppice willows, 1-year-old cuttings from three clones each of Salix pet-susu and Salix sachalinensis were planted and harvested after two-seasons growth under natural conditions. All cuttings were 20 cm long, with either 18 or 10 cm below ground level (referred to as deep planting [DP] and shallow planting [SP], respectively, hereafter). Aboveground dry biomass from DP was 40% greater than from SP, although root biomass did not differ between the two treatments and shoot number per cutting was lower for DP than SP. The roots of the DP cutting were found deeper in the soil than those of SP cutting, suggesting that sustained soil water supply resulted in the higher aboveground biomass.